Analysis of the Status and Trends of Chinese Clinical Practice Guideline Development Between 2010 and 2020: A Systematic Review - Zhang, Rong; Yan, Si-yu; Wang, Yun-yun; Huang, Qiao; Ren, Xiang-ying; Tan, Ran; Deng, Yu-qing; Su, Lin-xia; Wang, Yong-bo; Zhao, Zheng-rong; Jin, Ying-hui (Frontiers in Medicine, 2021)
Objective: The aim of this study was to systematically review the status and trends of Chinese CPGs during the time period 2010-2020 and explore their methodological characteristics. Then, based on the strengths and weaknesses in development, offer several recommendations for quality improvement which will serve as a reference for CPG users and developers. Introduction: With the development of evidence-based medicine, clinical practice guidelines (CPGs) play an increasingly important role in healthcare decision-making both in China and worldwide. Inclusion criteria: Clinical practice guidelines that have been used to help health professionals in healthcare decision-making were included. Methodology: CNKI and WanFang Database were searched from 2010 to 2020 for studies describing the general and methodological characteristics of Chinese clinical practice guidelines. Comparisons of methodological characteristics between groups were conducted using the chi-square test or Fisher’s exact test. The M-K test was adopted to identify monotonically increasing or decreasing trends of methodological characteristics over the timespan. Results: A total of 2654 CPGs fulfilled inclusion criteria. The quantity and quality of the guidelines developed in China have improved over the time span. From 2010 to 2020，the guidelines had differing characteristics and covered a wide range of subjects. 2318(87.34%) guidelines were focused on Western Medicine. Eight (0.30%) had been developed for patient versions of guidelines, 10(0.38%) were tentative guidelines and 16(0.60%) were rapid advice guidelines. Medical specialty societies (including their branches) (71.1%) were the main guideline makers. The most addressed diseases were neoplasms (14.43%). The target population is mainly adults (84.97%). The methodological quality of CB-CPGs was obviously lower than EB-CPGs. Except for the item, “recommendations were based on evidence of systematic reviews”, there were statistical differences in all other methodological items between EB-CPGS and CB-CPGS(P<0.01). Higher methodological quality has been observed in EB-CPGs. All the data relating to methodological characteristics indicated that higher methodological quality was present in guidelines using GRADE (P<0.01). Conclusion: The quantity and quality of the guidelines developed in China have improved between 2010 and 2020. CB-CPGs have also paid attention to methodology quality, but obviously, this is lower than that in EB-CPGs.